Intervensi koroner perkutan pada infark miokard akut disertai elevasi segmen ST awitan lebih dari 12 jam dengan penyulit syok kardiogenik - I Gusti Bagus Aginda Dwipawana; Vireza Pratama; Mia Amira Callista (DiscoverSys Inc., 2017)
Background: Percutaneous coronary intervention (PCI) is the primary therapy in patients with acute myocardial infarction with-ST Segment Elevation (AMI-STE) in the first 12 hours of onset of symptoms. However PCI still needs to be done in patients with onset more than 12 hours who still showed prolonged ischemia process. Case: A man, 49 years old came to the emergency room Central Army Hospital Gatot Subroto (RSPAD) with chest painÂ typically infarction angina since 6 days ago. Patient was referred from Islamic Hospital with anterior AMI-STE-onset 2 hours TIMI 7/14 Killip Class IV without revascularization and acute renal failure. Patient determined to be referred after treated in ICVCU Islamic Hospital, but patient had a progressive chest pain and hemodynamic disturbances. After revascularization in the RSPAD Hospital, clinical and hemodynamic conditions of this patient slowly improved. Discussion: Reperfusion therapy should be given if there is clinical evidence or evidence which showed prolonged ischemic ECG, even if the patient according to the symptoms have lasted more than 12 hours. It is because the onset of actual attack is certainly known. AMI-STE guidelines by ESC and AHA also recommend PCI procedure in patients with signs of prolonged ischemia process. Conclusion: Revascularization in patients with AMI-STE onset more than 12 hours should be performed in patients who still show a prolonged ischemia process and hemodynamic disturbances.